Customer complaints and the effectiveness of service guarantees in the hotel industry - Mohd Shahril, Aslinda; Abdul Aziz, Yuhanis (University of Rijeka, 2022)
Purpose – This study examines the relationship between service guarantee and service quality in four and five star hotels in Malaysia. It also examines the role of empowerment as a mediating variable between service quality and service guarantee, and between service guarantee and service recovery. Finally, this study examines the effectiveness of service recovery on customer satisfaction after unpleasant service experiences with the hotel. Design – The paper presents an exploratory analysis to examine the implementation of service guarantees in Malaysian hotels and the effect of empowerment on service guarantees and service quality from the customers' perspective. Methodology – This study focuses on the four and five star hotels in Malaysia. A survey through questionnaires distributed to the respondents who stayed at the hotel. To examine the relationship, the analysis is done using SPSS and AMOS for empirical analysis. Findings – The study found a significant relationship between service guarantee and service quality; service guarantee and empowerment and confirmed that empowerment mediates the relationship between service guarantee and service recovery. Originality of the research – The study is novel in its application of signalling theory to the study of service guarantee and service quality from the customer's perspective and with employee empowerment in the Malaysian hotel scenario.